The Effectiveness of Five Days School Program at Senior High School and Equivalent in Central Java: A Psychological and Academic View - Triyono, Triyono; Sari, Puji Novita; Lestari, Sari (Universitas Negeri Semarang, 2019)
Improvement for educational quality Indonesia is continually realized by the issuance of various policies, one of them is Minister of Education and Culture Regulation No. 23 of 2017 on School Day. This regulation stipulates that school days begin on Monday to Friday. Hence, the review of this policy is important to identify how extent the effectiveness of its implementation. This study aims to determine the effectiveness of the implementation of five days school program in terms of psychological aspects and academic aspects. Also, this research is conducted using a mix method design with sequential explanatory data analysis model. Results indicated that the effectiveness of five days school program implementation could be observed from its purposes and impacts. Based on the findings at the psychological aspect indicator, there are five indicators that have not met the standards of Minister of Education and Culture Regulation thus 5 days school has not been effective to develop psychological students, meanwhile from the academic aspect, overall research indicator is in accordance with expected standards hence 5 days school has been effective in supporting the academic development of students. This research serves as a reference for a stakeholder to make regulation and how to make an effective learning process that can solve students’ psychological during five days of school.